Type I interferon antagonistic properties of influenza B virus polymerase proteins. (8th December 2019) - Schreiber, André; Liedmann, Swantje; Brunotte, Linda; Anhlan, Darisuren; Ehrhardt, Christina; Ludwig, Stephan
Abstract: The innate immune system, in particular the type I interferon (IFN) response, is a powerful defence against virus infections. In turn, many if not all viruses have evolved various means to circumvent, resist, or counteract this host response to ensure efficient replication and propagation. Influenza viruses are no exception to this rule, and several viral proteins have been described to possess IFN‐antagonistic functions. Although the viral nonstructural protein 1 appears to be a major antagonist in influenza A and B viruses (IAV and IBV), we have previously shown that a specific motif in the IAV polymerase proteins exerts an IFN‐suppressive function very early in infection. The question remained whether a similar function would also exist in IBV polymerases. Here, we show that indeed a specific amino acid position (A523) of the PB1 protein in the IBV polymerase complex confers IFN‐antagonistic properties. Mutation of this position leads to enhanced activation of the IFN‐mediated signalling pathway after infection and subsequent reduction of virus titres. This indicates that inhibition of innate immune responses is a conserved activity shared by polymerase proteins of IAV and IBV.